2015
DOI: 10.1117/1.nph.2.4.041405
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of mesoscale optical recordings to assess regional, functional connectivity

Abstract: Abstract. With modern optical imaging methods, it is possible to map structural and functional connectivity. Optical imaging studies that aim to describe large-scale neural connectivity often need to handle large and complex datasets. In order to interpret these datasets, new methods for analyzing structural and functional connectivity are being developed. Recently, network analysis, based on graph theory, has been used to describe and quantify brain connectivity in both experimental and clinical studies. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…5 B ). Parietal cortex is widely regarded as a hub for integrating multisensory information in the mouse ( Kolb and Walkey 1987 ; Lim et al 2012 , 2015 ). It has been reported that sensory stimulation and photostimulation both induce propagated activity that terminates at a common sink in parietal association areas ( Mohajerani et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 B ). Parietal cortex is widely regarded as a hub for integrating multisensory information in the mouse ( Kolb and Walkey 1987 ; Lim et al 2012 , 2015 ). It has been reported that sensory stimulation and photostimulation both induce propagated activity that terminates at a common sink in parietal association areas ( Mohajerani et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical parcellation based on the spectral and spatial decomposition of the calcium signal resulted in 12 functional modules. 27,28…”
Section: Methodsmentioning
confidence: 99%
“…The temporal resolution is at the level of millisecond that is on par with electrophysiological recordings 19 23 The spatial resolution reaches 25 to 65 μm per pixel, and the size of imaged brain area is sufficient to record the signs of electrical activity over much of the dorsal mouse cortex, 24 1 cm2 area monkey’s cortex, 25 or 0.3 cm2 area over the cat cortex 26 . With these characteristics, voltage-sensitive dye imaging (VSDI) is an excellent technique to study neuronal dynamics over large cortical areas.…”
Section: Introductionmentioning
confidence: 99%